2014
DOI: 10.1136/heartasia-2014-010562
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of patients after mechanical valve replacement surgery for rheumatic heart disease in a developing country

Abstract: This first investigation of the HRQoL of people in a developing country after VR surgery for RHD found significant improvement from surgery with this improvement generally sustained. The lack of improvement in mental health requires further exploration as does the influence of an isolated MVR, age and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…In our study, all patients perceived that their HRQoL was impaired pre-operatively with a mean (±SD) score of 3.47 ± 0.59 on a global scale, and 3.49 ± 0.59, 3.43 ± 0.64, 3.44 ± 0.69 in the emotional, physical and social domains respectively. Our findings are similar to that reported in a study done by Mangnall et al [ 10 ] which showed that preoperatively all mean HRQoL eight domains scores were much lower than the reference population with severe impairment in the general health and physical function domains. Similarly, Joshi et al [ 39 ] reported that the HRQoL was impaired in all eight domains with the lowest scores in the general health and physical function domain before surgery (15.61 ± 1.30), which improved after surgery (22.95 ± 0.45).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, all patients perceived that their HRQoL was impaired pre-operatively with a mean (±SD) score of 3.47 ± 0.59 on a global scale, and 3.49 ± 0.59, 3.43 ± 0.64, 3.44 ± 0.69 in the emotional, physical and social domains respectively. Our findings are similar to that reported in a study done by Mangnall et al [ 10 ] which showed that preoperatively all mean HRQoL eight domains scores were much lower than the reference population with severe impairment in the general health and physical function domains. Similarly, Joshi et al [ 39 ] reported that the HRQoL was impaired in all eight domains with the lowest scores in the general health and physical function domain before surgery (15.61 ± 1.30), which improved after surgery (22.95 ± 0.45).…”
Section: Discussionsupporting
confidence: 92%
“…In sub-Saharan Africa, patients present late in hospital with advanced stage of RHD requiring interventions such as heart valve replacement (HVR) [ 7 – 9 ]. Effectiveness of surgical interventions such as HVR has been traditionally assessed based on morbidity and mortality outcomes [ 10 , 11 ]. However, the impact of these interventions on the patient’s perspective assessed by patient-reported outcome measures (PROMs) is as well an important component of effectiveness as the symptomatic and functional status improvement [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“… 75 For example, Thomson Mangnall et al ’s 75 study with Indigenous Fijian participants (aged 12-55 years) substituted the example ‘Moderate activities, such as bowling, vacuuming, playing golf’ for ‘Moderate activities, such as moving a table, sweeping the floor, swimming, or gardening’. 75 Written authorisation was obtained for these changes from the SF-36v2 international licencer. However, considerable doubt still remains as to the relevancy of the concepts and dimensions in relation to Indigenous populations.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients report lower levels of HRQOL following medical procedures, due to postoperative pain, sleep disturbance, memory problems, and disrupted social interactions by the surgery [ 5 ]. On the other hand, among patients with advanced heart failure, surgical treatment might decrease or eliminate symptoms, and significantly improve physical functioning and decrease need for pharmacotherapy, leading to an improvement in overall wellbeing and quality of life [ 6 ].…”
Section: Introductionmentioning
confidence: 99%